Analysis Of The Implementation Of The Internal Control System In Fixed Asset Management (Case Study On: University Of Muhammadiyah Sukabumi) - Resti Heriyanti; Sulaeman (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Universities as higher education institutions play an important role in producing competent human resources. One of the key elements in supporting university operations is the availability of supporting facilities and infrastructure that are classified as fixed assets. Effective and efficient asset management is very important to ensure the success of the education process. However, based on observations at the Muhammadiyah University of Sukabumi (UMMI), several problems were found in the management of fixed assets, such as lack of asset identification, storage of damaged assets, and lack of maintenance. This can be caused by a weak internal control system. The purpose of this study is to analyze the Implementation of the Internal Control System in Fixed Asset Management at the Muhammadiyah University of Sukabumi based on the COSO Internal Control components, namely, control environment, control activities, risk assessment, information and communication, and monitoring. This study uses a descriptive qualitative research method with data collection techniques through observation, interviews and documentation. The results of this study indicate that the management of fixed assets at UMMI which is applied based on the theory put forward by COSO has shown several strengths, such as a clear organizational structure with separation of duties and authorities, and the use of effective information systems. However, there are still some areas that need improvement, such as the lack of specific training for employee competency development and constraints in storing damaged goods and maintaining barcodes on old fixed assets. Nevertheless, UMMI has shown commitment in conducting risk assessments and periodic monitoring, including audits by the Internal Audit Unit (SPI). Overall, the fixed asset management system and internal control at UMMI have been running quite effectively, but there is still room for improvement to increase the efficiency and effectiveness of fixed asset management in the future.